Possibilities of sublingual allergen-specific immunotherapy in preschool children with sensitization to mold fungus allergens - O. V. Sharikadze; O. M. Okhotnikova (Zaporozhye State Medical University, 2020)
Purpose. Determination of the efficacy of sublingual allergen-specific immunotherapy (SLIT) in preschool children with sensitization to allergens of mold Alternaria alternata. Materials and methods. The study involved 447 children aged 4.1 ± 0.9 years (from 3 to 7 years old), with verified diagnoses of allergic bronchial asthma and/or allergic rhinitis. In 58 patients with proven sensitization to Alternaria alternata major allergens, the efficacy of sublingual allergen-specific immunotherapy (SLIT) was assessed, which was carried out for 3 years and evaluated using a visual analogue scale (VAS) and the sIgE level to the major component of Alternaria Alt a1. 27 children (group II) who received exclusively basic therapy were included in the comparison group. Results. During three years, SLIT in patients of the first group showed a significant decrease in the frequency of nasal symptoms: sneezing from 29 (26; 31) mm to 8 (6; 11) mm (P = 0.008), rhinorrhea from 29 (26; 34 ) mm to 5 (4; 6) mm (P = 0.012) mm, itching from 20 (17; 23) mm to 5 (4; 6) (P = 0.002) mm and nasal congestion from 29 (25; 35) mm to 7 (5; 9) mm (P = 0.016) compared with the initial level. Similar dynamics were observed with the nasal symptoms itching of the eyes, redness of the eyes and discharge from the eyes, which significantly decreased from 26 (23; 31) mm to 5 (3; 7) mm (P = 0.007), from 29 (26; 36) mm to 4 (3; 6) mm (P = 0.014) and from 29.5 mm to 5.0 (4; 7) mm (P = 0.003) in comparison with the initial values. Dynamics were also observed in relation to asthma symptoms, namely, the cough and shortness of breath indices reliably decreased from 54 (46; 61) mm to 7 (6; 9) mm (P = 0.013) and from 50 (39; 57) mm to 7 (5; 9) mm (P = 0.011) compared to baseline values. It should be noted that the indicators of VAS in children after the end of the SLIT course were significantly lower than those in children who received basic therapy. Conclusions. The study showed that the use of sublingual immunotherapy in children with sensitization to mold Alternaria alternata and the presence of clinical manifestations of allergic rhinitis and / or allergic bronchial asthma, is an effective and safe treatment method and allows to gain control over symptoms of the disease quickly (within the first 6 months).